Taxonomic revision of the Dichotomius sericeus (Harold, 1867) species group (Coleoptera: Scarabaeidae: Scarabaeinae) - Valois, Marcely C.; Vaz-De-Mello, Fernando Z.; Silva, Fernando A. B. (Zootaxa, 2017)
The Dichotomius sericeus species group of the subgenus Luederwaldtinia is reviewed. This group comprises eight species endemic to the South American Atlantic forests, Caatinga and associated areas of Brazil, Paraguay and Argentina: Dichotomius sericeus (Harold, 1867); Dichotomius irinus (Harold, 1867); Dichotomius laevicollis (Felsche, 1901); Dichotomius schiffleri Vaz-de-Mello, Gavino & Louzada, 2001; Dichotomius guaribensis sp. nov.; Dichotomius gilletti sp. nov; Dichotomius iannuzziae sp. nov; and Dichotomius catimbau sp. nov. Lectotypes are designated for D. sericeus (Harold, 1867), D. irinus (Harold, 1867), D. laevicollis (Felsche, 1901) and D.sericeus var. aterrimus (Luederwaldt, 1929) [here synonymized with D. sericeus]. In this revision each species is analyzed as follows: a detailed literature review, a diagnosis, description, illustrations of key morphological characters, list of material examined and a geographic distribution.